Media-Driven Sociocultural Pressures and Disordered Eating among Medical and Paramedical Students in Chengalpattu, Tamil Nadu: A Cross-Sectional Study - Masthan, Mohamed Farris; Edward, Shanthi; Ilaval, Ilam T; Chander, J Karunya; Kumaran, Saranya (National Journal of Community Medicine, 2026)
Background: The rising prevalence of disordered eating among the young population is primarily driven by sociocultural pressures that promote idealised body images. Medical college students deal with academic demands and social pressures while being increasingly exposed to appearance-focused media. The objective was to estimate the prevalence of disordered eating and its relationship with sociocultural pressures amongst college students in Tamil Nadu. Methodology: This cross-sectional study included 332 undergraduate medical and paramedical students from a tertiary care centre in Tamil Nadu. Sociocultural pressures and disordered eating were assessed using SATAQ-4 and EDE-QS. Associations were analysed using Chi-square tests with odds ratios (95% CI) and Spearman's correlation coefficient (ρ) using SPSS v25. Results: The prevalence of disordered eating was 45.8% (95% CI: 40.4-51.3%). High sociocultural pressure tripled the odds of disordered eating (OR=3.21; 95% CI: 2.03-5.08; p<0.001). Media pressure had the strongest relationship with disordered eating, showing both higher odds (AOR = 2.54, 95% CI: 1.49-4.32, p < 0.001) and the highest correlation (ρ=0.448, p<0.001). Females showed greater odds of disordered eating than males. No significant difference was observed between medical and paramedical students. Conclusions: Media-driven sociocultural pressures fuel disordered eating among college students, highlighting the need for targeted media literacy and psychosocial interventions.